Implikasi Yuridis Wanprestasi dan Perbuatan Melawan Hukum Medis Pasca Berlakunya Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan - Inna Noor Inayati (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The enactment of Law Number 17 of 2023 concerning Health has brought fundamental changes to the civil liability mechanism for medical malpractice in Indonesia. This research aims to analyze the theoretical transformation and judicial implications of the dualism of medical breach of contract (wanprestasi) and tort (PMH) claims following the implementation of this regulation. The research method used is normative legal research with statutory and conceptual approaches. The results indicate that Article 308 paragraph (2) of Law Number 17 of 2023, which requires a recommendation from the Professional Disciplinary Board for civil claims against individual medical personnel, creates significant procedural hurdles in tort claims. This has implications for a shift in patient litigation strategies, which tend to opt for breach of contract or tort claims directed at Health Service Facilities based on the Corporate Liability doctrine. Furthermore, Article 275 paragraph (2) reinforces the exemption from compensation in emergency conditions as a form of professional protection. In conclusion, Law Number 17 of 2023 strengthens procedural protection for medical personnel while simultaneously encouraging the centralization of civil liability burdens on healthcare institutions.